Implementation of an Automated Electronic Medical Record "Antibiotic Timeout" Alert at a Tertiary, Academic Medical Center. (4th October 2017) - James, Charles; Coates, Carrie; Clay, Brian; Abeles, Shira
Abstract: Background: An antibiotic timeout (ATO) is a relatively new regulatory requirement for antibiotic stewardship programs. An ATO is a mandatory review of the antibiotics being prescribed to inpatients on approximately day three of antibiotic therapy. Its purpose is to encourage appropriate de-escalation or discontinuation of antibiotics as more clinical data is available on which to base antibiotic choices. The primary objective of this study is to describe the impact of implementing an electronic "antibiotic timeout" (ATO) on antibiotic de-escalation at an academic medical center. Methods: We implemented an electronic medical record (EMR) based ATO in August 2016 at a tertiary academic medical center. We leveraged native alerting functionality in the EMR to present a notification to the primary clinician after a patient had received intravenous vancomycin (V) and/or piperacillin/tazobactam (Z) for more than 48 hours. The 'best practice alert' (BPA) reminded the clinician to review the appropriateness of antibiotic selection and to attest to this action. Results: After implementation of this ATO, we reviewed a random sampling of 100 patients initiated on V and/or Z therapy for whom providers received an automated ATO notification and compared antibiotic use to 100 patients who received the same therapy prior to the ATO implementation. We found an overall increase in de-escalation (defined as either changing or stopping therapy) on day 3 of V and/or Z therapy from 27% pre-ATO to 70% for post-ATO. For overall V therapy, we found a de-escalation from 27% pre-ATO to 68% for post-ATO and for overall Z therapy, we found a de-escalation from 25% pre-ATO to 72% for post-ATO. Conclusion: An EMR generated BPA ATO had a significant impact on de-escalation of V and/or Z on day 3 of therapy. Disclosures: All authors: No reported disclosures.